INFLUENCE OF TARBIYYAH IN CONSUMER EDUCATION AND ADVOCACY IN EMPOWERING INDIVIDUAL CONSUMERS FOR EFFICIENT CONSUMER PROTECTION - Mhd Sarif , Suhaimi; Ismail, Yusof; Zainudin, Dolhadi (Online Journal of Islamic Management and Finance (OJIMF), 2023)
This paper investigates the effect of tarbiyyah (a systematic education system) on consumer education and advocacy, concentrating on its role in empowering individuals for effective consumer protection. The purpose of this study is to determine how tarbiyyah influences consumer behaviour and promotes responsible consumption, thereby contributing to Sustainable Development Goal 12 (SDG 12) on responsible consumption. An in-depth examination of the experiences and viewpoints of three consumer advocates who are included in the research’s scope is made possible via qualitative personal interviews. Two primary research objectives have been identified: first, to examine the effect of tarbiyyah on consumer education and awareness; and second, to evaluate its efficacy in empowering individuals to safeguard their rights as consumers. The results emphasise the importance of a structured tarbiyyah education system in influencing consumer behaviour and encouraging responsible consumption. The study highlights the pragmatic ramifications for consumer associations and civic organisations involved in promoting conscientious consumer behaviour, underscoring the significance of incorporating tarbiyyah principles into their instructional curricula. By offering insights into empowering people for effective consumer protection, this research adds to the general knowledge of the function of tarbiyyah in consumer education and advocacy. The study has a limitation in that it is based solely on three consumer advocates, which may not fully represent the broader consumer population. While this sample size is suitable for qualitative research to ground insights, it may not effectively capture quantitative aspects and statistical significance. Nonetheless, the study still offers valuable insights into the potential impact of tarbiyyah on consumer behavior. and its contribution to Sustainable Development Goal 12.